2016
DOI: 10.3109/01443615.2015.1103716
|View full text |Cite
|
Sign up to set email alerts
|

The effects of prolonged fasting on the levels of adiponectin, leptin, apelin, and omentin in pregnant women

Abstract: The aim of the present study was to evaluate serum adiponectin, leptin, apelin and omentin levels to explore metabolic changes occurring during fasting in the month of Ramadan. The study was designed as a prospective study. The patients were divided into two groups, each comprising 20 patients: Group I, fasting pregnant women, and Group II, non-fasting pregnant women. The patients' age, parity, gestational week and body mass index were recorded. Adiponectin and omentin levels were significantly lower in fastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…For women with diabetic pregnancy, the circulating level of adiponectin is low, and this is associated with increased fetal growth [29]. Adiponectin and omentin levels are markedly lower in fasting than non-fasting pregnant women [30]. The decreased serum omentin-1 level may be also related to increased fetal growth.…”
Section: Discussionmentioning
confidence: 99%
“…For women with diabetic pregnancy, the circulating level of adiponectin is low, and this is associated with increased fetal growth [29]. Adiponectin and omentin levels are markedly lower in fasting than non-fasting pregnant women [30]. The decreased serum omentin-1 level may be also related to increased fetal growth.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 494 articles that were retrieved, 20 were included in the meta-analysis; four were apelin studies [4,6,7,11], nine were chemerin studies [5,8,15,16,[23][24][25][26][27], five were omentin studies [28][29][30][31][32], one study involved both apelin and omentin [12], and one study involved both chemerin and omentin [33]. The 20 studies enrolled 2981 participants, of which 1493 were GDM patients and 1488 were healthy pregnant women (controls) [4-8, 11, 12, 15, 16, 23-33] (Fig.…”
Section: Literature Research and Characteristics Of The Included Studiesmentioning
confidence: 99%
“…Elsehmawy et al [10] have described apelin as a novel adipokine that is produced and secreted by mature human adipocytes. Studies of serum or plasma apelin concentration in GDM patients by Baris et al found lower circulating apelin in women with GDM than in controls; however, Emel et al reported an increased apelin concentration in GDM patients [11,12].…”
Section: Introductionmentioning
confidence: 98%
“…Nevertheless, the correlation of APLN levels with GDM has not yet reached an agreement in clinical researches. Three studies reported a decrease of serum APLN level in GDM patients (Aydin, 2010;Boyadzhieva et al, 2013;Akinci et al, 2014) while two other groups revealed an increase (Aslan et al, 2012;Caglayan et al, 2016). In contrast, there were also no significant association reports between normal control and GDM patients (Telejko et al, 2010;Oncul et al, 2013).…”
Section: Regulation Of Apela and Apln In Pementioning
confidence: 98%